Corrigendum: Biomarkers of Skin Graft Healing in Venous Leg Ulcers - Klaus Kirketerp-Møller; Petra Doerfler; Nicole Schoefmann; Barbara Wolff-Winiski; Omid Niazi; Vibeke Pless; Tonny Karlsmark; Magnus S. Ågren (Medical Journals Sweden, 2022)
Abstract is missing (Corrigendum)